Enhanced remediation of Cr6+ in bacterial‐assisted floating wetlands. (11th March 2020) - Akram, Aysha; Tara, Nain; Khan, Muhammad Asaf; Abbasi, Saddam Akber; Irfan, Muhammad; Arslan, Muhammad; Afzal, Muhammad
Abstract: Hexavalent chromium (Cr 6+ ) is reported to have negative effects on fauna and flora. The present study establishes plant‐bacterial synergism in floating wetlands (FWs) for the maximum removal of Cr 6+ from the contaminated water. A common wetland plant, Brachiaria mutica (para grass), was planted in combination with three Cr‐resistant rhizo‐ and endophytic bacteria. Results indicated that FWs vegetated with B. mutica showed the potential to remove Cr (53%) from water and their efficacy was significantly enhanced by bacterial inoculation (88%). The inoculated bacteria were able to colonize the plant interior successfully, that is, roots and shoots. The un‐vegetated control tanks, however, showed the least bacterial persistence in the water. The perceptible phytotoxicity symptoms on B. mutica were only observed for the treatments without bacterial inoculation. The study suggests that B. mutica could be an effective choice as a wetland macrophyte to establish a partnership with the Cr‐resistant bacteria for improved remediation of Cr 6+ contamination.